Role of hyaluronidase as an adjuvant in local anesthesia for cataract surgery - Arthi Mohankumar; Mohan Rajan (Indian Journal of Ophthalmology, 2023)
Cataract surgery ranks among the commonest procedures performed worldwide. Approximately 51% of blindness worldwide is related to cataracts, affecting about 65.2 million people worldwide and more so in developing countries. Over the years, there has been a significant evolution in the surgical techniques of cataract extraction. The advancement in phacoemulsification machines, phaco-tips, and the availability of ophthalmic viscoelastic devices have played a substantial role in cataract surgery such that they are faster and more controlled than before. Similarly, anesthetic techniques in cataract surgery have advanced significantly from retrobulbar, peribulbar, and sub-Tenon's blocks to topical anesthesia. Though topical anesthesia eliminates the possible complications of injectable anesthesia, it is not suitable for use in uncooperative, anxious patients, pediatric age groups, and patients with cognitive disabilities. Hyaluronidase is an enzyme that breaks down hyaluronic acid in the retrobulbar tissue, facilitating uniform diffusion of the anesthetic drug and hastening the onset of anesthesia and akinesia. Hyaluronidase has been used in the last 80 years successfully as an adjuvant in retrobulbar, peribulbar, and sub-Tenon's blocks. Initially, the hyaluronidase enzyme was animal-derived and of bovine and ovine sources. Recombinant human-derived hyaluronidase, which has lesser allergic reactions, impurities, and toxicity, is now available. There is conflicting evidence regarding the efficacy of hyaluronidase as an adjuvant in retrobulbar and peribulbar blocks. This article summarizes a brief review of the literature on the role of hyaluronidase as an adjuvant in local anesthetic blocks in ophthalmic surgeries.